La ciudad como fenómeno ecológico - Higueras Arnal, Antonio (Geographicalia, 2017)
In this paper we try to make clear that BARROWS proposal (1923) considering Human Geography facts as Humen Ecology facts reveals an interesting method of geographical analysis with renovated actualify. Some rnethodological and conceptual considerations about the validity to the geographer of this analysis are made in the introduction. Then, the analysis is applied to the study of cities as ecological phenomena.